2019
DOI: 10.3390/rs11242963
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Post-Fire Recovery of Chaparral and Conifer Species Using Field Surveys and Landsat Time Series

Abstract: Recovery trajectories derived from remote sensing data are widely used to monitor ecosystem recovery after disturbance events, but these trajectories are often retrieved without a precise understanding of the land cover within a scene. As a result, the sources of variability in post-disturbance recovery trajectories are poorly understood. In this study, we monitored the recovery of chaparral and conifer species following the 2007 Zaca Fire, which burned 97,270 ha in Santa Barbara County, California. We combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 82 publications
0
11
0
1
Order By: Relevance
“…As a result of this property, NDVI is considered an appropriate vegetation index to study vegetation patterns across temporal or spatial scales and it has been extensively used to study post-fire landscape patterns and vegetation dynamics [79,[81][82][83][84]. Although other indices are also reported in the literature as suitable to monitor post-fire vegetation recovery, such us the Normalised Burn Ration (NBR) [77,78,85], NDVI was the first one tried in this study and gave excellent results. The NDVI values theoretically range between -1 and 1 but this range is never achieved since a given pixel will always have some reflectance in both the IR and R bands.…”
Section: Remote Sensing Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…As a result of this property, NDVI is considered an appropriate vegetation index to study vegetation patterns across temporal or spatial scales and it has been extensively used to study post-fire landscape patterns and vegetation dynamics [79,[81][82][83][84]. Although other indices are also reported in the literature as suitable to monitor post-fire vegetation recovery, such us the Normalised Burn Ration (NBR) [77,78,85], NDVI was the first one tried in this study and gave excellent results. The NDVI values theoretically range between -1 and 1 but this range is never achieved since a given pixel will always have some reflectance in both the IR and R bands.…”
Section: Remote Sensing Methodsmentioning
confidence: 90%
“…Since 1982, when Landsat 4 was launched, the spatial resolution is stable at 30 m for the multispectral products. Due to the long timespan of Landsat data availability they are quite extensively used to build time series datasets for long term monitoring of post fire succession and vegetation dynamics, both at the green cover level and at the community level [75][76][77][78][79][80].…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…When comparing the number of BCDF stands that were classified into their respective mortality and burn severity classes, we found that the RdNBR burn severity classes commonly did not associate with the same mortality classification. In both fires, remotely sensed RdNBR significantly overestimated the number of stands with high and moderate mortality and significantly underestimated the number of stands with no and low mortality compared to visual assessment, perhaps due to the sensitivity of RdNBR to fire impacts on the understory (Kibler et al, 2019).…”
Section: Visual Mortality Vs Rdnbr As the Response Variablementioning
confidence: 92%
“…Resilience to fire in terms of vertical structure diversity recovery Remote sensing estimates of VSD revealed that none of the plant communities dominated by shrub or tree species have recovered to a prefire state in the short term (4 years after fire disturbance), although their VSD values have increased progressively over the time series. Previous remote sensing research was conducted in similar Mediterranean plant communities in the western Mediterranean Basin (Fernández-Guisuraga et al, 2020; as well as chaparral shrublands in California (Kibler et al, 2019;Storey et al, 2016), evidenced that vegetation cover reached prefire conditions in the short-term after wildfire disturbance. These studies used fractional vegetation cover (FVC) as an engineering resilience indicator retrieved from passive optical data by means of vegetation indices, pixel unmixing models, and radiative transfer models.…”
Section: Extrapolation Of C-band Sar and Optical Predictive Relations...mentioning
confidence: 94%